The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4056/sigs.5429581
|View full text |Cite
|
Sign up to set email alerts
|

High quality draft genome sequence of Staphylococcus cohnii subsp. cohnii strain hu-01

Abstract: Staphylococcus cohnii subsp. cohnii belongs to the family Staphylococcaceae in the order Bacillales, class Bacilli and phylum Firmicutes. The increasing relevance of S. cohnii to human health prompted us to determine the genomic sequence of Staphylococcus cohnii subsp. cohnii strain hu-01, a multidrug-resistant isolate from a hospital in China. Here we describe the features of S. cohnii subsp. cohnii strain hu-01, together with the genome sequence and its annotation. This is the first genome sequence of the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
1
8
0
Order By: Relevance
“…Often methicillin resistance occurs in combination with resistance to other various antimicrobials. 22,23 After susceptibility testing to other antibiotic groups, in this study we found that the MRSA isolates from blood cultures (at 39.2%) were predominated compared to those from abscesses (15.6%) (p=0.01). The isolates from group I were from inpatients with bacteriemia.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Often methicillin resistance occurs in combination with resistance to other various antimicrobials. 22,23 After susceptibility testing to other antibiotic groups, in this study we found that the MRSA isolates from blood cultures (at 39.2%) were predominated compared to those from abscesses (15.6%) (p=0.01). The isolates from group I were from inpatients with bacteriemia.…”
Section: Discussionmentioning
confidence: 55%
“…This suggests that there is a difference in the origin of the causative agent -community acquired or hospital acquired, which is more frequently described as a reason for increasing the health care-associated infections in relation to MRSA and MRSCoNS. 6,17,22 MLS resistance that did not correlate with hospital acquired infections. Moreover, a dramatic increase in clindamycin resistance among S. aureus isolates has been described.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…DSM 20610 T was grown aerobically on a Columbia blood agar base at 37°C for 24 h. Genomic DNA was extracted using the DNeasy blood and tissue kit (Qiagen, Germany), as described earlier ( 8 ). Whole-genome sequencing was performed at the State Key Laboratory for Diagnosis and Treatment of Infectious at Zhejiang University using an Illumina HiSeq 2000 genomic sequencer.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Till date, 35 species are whole genome sequenced, assembled and annotated some of these are: Staphylococcus aureus strain N315 [3], Staphylococcus carnosus strain TM 300 [4], Staphylococcus epidermidis strain ATCC 1228 [5], Staphylococcus haemolyticus strain JCSC 1435 [6], Staphylococcus lugdunensis strain HKU09-01 [7], Staphylococcus pseudointermidus strain ED 99 [8], Staphylococcus saprophyticus strain ATCC 15305 [9], Staphylococcus warneri strain SG 1 [10], Staphylococcus xylosus strain SMQ-121 [11] and Staphylococcus cohnii subsp. cohnii [12]. Various members of the genus Staphylococcus are commensals and inhabitant of the skin and upper respiratory tracts of mammals [13].…”
Section: Introductionmentioning
confidence: 99%